“Minute ten”: a peruvian educational alternative for the teaching of communication and development of understanding - Soto Acosta, Rocío del Carmen (2023)
The pedagogical approach to strategies for the improvement of students’ reading comprehension is one of the main challenges of education in Peru. In the case of the Tacna region, this improvement has gone hand in hand with educational innovation, mainly during the transition period between the exams to control the evolution of educational parameters proposed as part of the Student Census Evaluation Strategy (ECE) promoted by the Ministry of Education, as a response to the low indicators in mathematical and verbal reasoning of Peruvian students. The objective of this research is to demonstrate the impact of the "Minute Ten" strategy in improving the results of students in the Tacna Region. To demonstrate this, a comparison of pre- and post-implementation results of the strategy will be made to understand its impact on students in the Tacna Region, Peru.